2023
DOI: 10.3390/cancers15072007
|View full text |Cite
|
Sign up to set email alerts
|

Association between Chronic Gingivitis and Cancer: A Retrospective Cohort Study of 19,782 Outpatients from the United Kingdom

Abstract: Purpose: Recent data argue for the involvement of inflammatory and infectious diseases in cancer development. However, clinical data on the association between chronic gingivitis and cancer have been less conclusive. Here, we systematically evaluated the cancer incidence in a population-based cohort of outpatients with chronic gingivitis from the United Kingdom. Methods: 9891 patients with chronic gingivitis and an identical number of people without gingivitis matched by age, gender, index year, and the Charls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…For example, Verma et al [ 36 ] conducted a meta-analysis that showed that chronic periodontitis can increase the incidence of lung cancer. Beger-Luedde et al [ 37 ] in a retrospective study of 19,782 individuals in the UK, Beger-Luedde et al found a significantly higher risk of various types of cancer (including breast cancer, lymphoid system cancer, and digestive tract cancers) in patients with chronic gingivitis, particularly prostate cancer. However, the specific mechanisms underlying the association between periodontal diseases and tumors remain unclear, and some researchers have suggested that it may be a combination of systemic inflammatory responses, immune stress, and microbial dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Verma et al [ 36 ] conducted a meta-analysis that showed that chronic periodontitis can increase the incidence of lung cancer. Beger-Luedde et al [ 37 ] in a retrospective study of 19,782 individuals in the UK, Beger-Luedde et al found a significantly higher risk of various types of cancer (including breast cancer, lymphoid system cancer, and digestive tract cancers) in patients with chronic gingivitis, particularly prostate cancer. However, the specific mechanisms underlying the association between periodontal diseases and tumors remain unclear, and some researchers have suggested that it may be a combination of systemic inflammatory responses, immune stress, and microbial dysbiosis.…”
Section: Discussionmentioning
confidence: 99%